O Programa de Aquisição de Alimentos e seu papel no fomento a inclusão social no campo - Moreno, Blesser Tavares (2012)
The purpose of this dissertation was to analyze and evaluate the implementation of the Food Acquisition Program - EAP that is part of the Policy for Food Security and Nutrition. This program is intended for the purchase of agricultural products that are produced by Family farmers falling within the National Program for Strengthening Family Agriculture - PRONAF. The PAA was established in 2003 and has the function of distributing food purchased from farmers to different entities that deal with people in a situation of food and nutritional insecurity. The focus of this study was to analyze the impact of the PAA in the composition of the income of beneficiary families in the program, especially among those poorer families. Another point discussed was the role of it in the Family strengthening agriculture in view of the strong concentration of traders in the market for fresh produce, where these products are intended for the Supply-supply structures, located in the municipality of Tianguá beside the municipality Viçosa do Ceará. The methodological procedures used in this project were based on an analytical study of the implementation of the EAP in Viçosa do Ceará, in 2010. The analysis relied on methodology based on research literature, documentary and field research quantitative and qualitative, have been interviewed farmers and institutions that operationalize the program. The PAA has proven to be a key element in the generation of income, where the respondents considered the program to be relevant in local terms, besides acting in the maintenance of the family group. In addition, it operates in strengthening family agriculture. The negative side of it, we highlight the issue of seaso.